Correlation between asymmetric profiles in slits and standard prewetting lines - Leszek Szybisz; Salvador A. Sartarelli (Papers in Physics, 2009)
The adsorption of Ar on substrates of Li is investigated within the framework of a density functional theory which includes an effective pair potential recently proposed. This approach yields good results for the surface tension of the liquid-vapor interface. The behavior of the adsorbate in the cases of a single planar wall and a slit geometry is analyzed as a function of temperature. Asymmetric density profiles are found for fluid confined in a slit built up of two identical planar walls leading to the spontaneous symmetry breaking (SSB) effect. We found that the asymmetric solutions occur even above the wetting temperature $T_w$ in a range of average densities $ho^*_{ssb1} le ho^*_{av} le ho^*_{ssb2}$, which diminishes with increasing temperatures until its disappearance at the critical prewetting point $T_{m cpw}$. In this way a correlation between the disappearance of the SSB effect and the end of prewetting lines observed in the adsorption on a one-wall planar substrate is established. In addition, it is shown that a value for $T_{m cpw}$ can be precisely determined by analyzing the asymmetry coefficients.